Evolution and devolution: Scottish legislation relevant to people with intellectual disabilities within mental health and forensic services. (14th December 2015) - Douds, Fergus; Haut, Fabian
Abstract : Purpose: – The purpose of this paper is to describe the evolution of legislation relevant to people with intellectual disabilities (IDs) since the Scottish Parliament came into being in 1999; this will be particularly relevant to practitioners working with people with IDs within mental health and forensic mental health services. Design/methodology/approach: – A descriptive review of the relevant legislation, setting this out in the chronological order in which the legislation was enacted. Findings: – The paper demonstrates that legislative reform is a dynamic and evolving process, responsive to social, political and legal agendas. Research limitations/implications: – The paper is limited to a description of the relevant legislation in only one part of the UK (Scotland). Practical implications: – A helpful summary of the relevant legislation is provided which should be of particular value to readers/practitioners from outwith Scotland. Originality/value: – The paper provides an up to date account of the legislative reform in Scotland during the period 1999-2015.